Crop-to-wild introgression in the European wild apple Malus sylvestris in Northern Britain. (28th September 2018) - Ruhsam, Markus; Jessop, Will; Cornille, Amandine; Renny, James; Worrell, Rick
Abstract: Malus sylvestris (L.) Mill, the European wild apple, is a small tree native to Europe which reaches its north-western limit in Northern Britain. It has been identified as one of the main contributors to the domesticated apple M. domestica (Suckow) Borkh. There are concerns that wild populations of this rare tree are threatened by hybridization with M. domestica throughout Europe. We genotyped 332 trees collected in the wild from Scotland and Northern England using 14 microsatellite markers to investigate levels of introgression in wild M. sylvestris populations. Our results showed that 70 per cent of the samples could be considered pure M. sylvestris, 27 per cent showed varying degrees of introgression from M. domestica and 3 per cent were pure M. domestica . Hybrids were more frequent in areas with more intensive land use and less semi-natural woodland. About 80 per cent of hybrids were identified as backcrosses to M. sylvestris. Areas in the Southern Highlands had the highest frequency of pure M. sylvestris trees (87 per cent). Morphological characters such as leaf size and hairiness as well as fruit size generally used by botanists for identification of M. sylvestris in the field proved to be unreliable as only 68 per cent of the trees could be identified accurately. Given the use of wild apple trees it seems likely that many of the trees collected from agricultural areas are planted and not the product of natural in situ hybridization and seed dispersal events thus compounding natural hybridization rates. Areas with high frequencies of pure M. sylvestris trees should be prioritized for conservation and possible measures are discussed to safeguard M. sylvestris as a species in Northern Britain.